THE EFFECT OF IRON (III)-HYDROXIDE POLYMALTOSE COMPLEX ON ANEMIA: A LITERATURE STUDY - Insani, Indah; Siregar, Vrili; Girsang, Osi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Health is an important thing to be maintained in life. In the development of this era, many people, especially teenagers, do not pay attention to the intake of nutrients, iron, and protein that enter the body causing disease. One of the diseases that can be caused is anemia. According to the National Institute of Health (NIH) the cause of anemia can be caused by a lack of iron, vitamins, or chronic disease. In Indonesia, the occurence of anemia is fairly high. still quite high. To overcome anemia, iron complex compounds can be used because one of the things that causes anemia is a lack of iron in the body. This study aims to describe the application of iron (III)-hydroxide polymaltose complex as an effective compound in overcoming of iron deficiency anemia.This study was compiled from the online literature of local and international journals using secondary data that had been screened based on keywords. The results of the study concluded that iron (III)-Hydroxide Polymaltose Complex Compounds can be used to treat anemia.This literature study covers recently published (year > 2000) reports on iron (III)-Hydroxide Polymaltose Complex Compounds in overcoming the health problem of anemia.